Analysis of Sound Elements in Poetry “Kita saksikan” Sapardi Djoko Damono's Stylistic Study - Anggi Triandana; Lia Rahmayanti (Proceeding International Conference on Malay Identity, 2021)
Abstract: This study aims to describe the phonological aspect of 'Kita Saksikan' poem by Sapardi Djoko Damono. This study uses a qualitative descriptive method to explain the results of phonological aspect in Sapardi Djoko Damono's poem ‘Kita Saksikan’. Based on the results of the stylistic studies that have been carried out, it can be concluded that the poem 'Kita Saksikan' by Sapardi Djoko Damono is a type of poetry that has an efony orchestrated sound. Phonological elements in the form of alliteration are /d/, /k/, /l/ , /m/, /n/, /p/, /r/, /s/ and /t/ , assonance sounds are /a/, /u/, /i/ and /e/. The final rhyme is in the form of a-a-a-a, the inner rhyme is in the form of an, ak and am sounds.